1993
DOI: 10.1111/j.1432-1033.1993.tb18383.x
|View full text |Cite
|
Sign up to set email alerts
|

19F‐NMR study on the pH‐dependent regioselectivity and rate of the ortho‐hydroxylation of 3‐fluorophenol by phenol hydroxylase from Trichosporon cutaneum

Abstract: The regioselectivity and rate of the ortho-hydroxylation of 3-fluorophenol by phenol hydroxylase from Trichosporon curuneum (EC 1.14.13.7) was studied using 19F-NMR. The regioselective hydroxylation as well as the rate of orrho-hydroxylation are pH dependent with a pKa of 6.5. At pH values below 6.5, 3-fluorophenol preferentially becomes hydroxylated at the C6 ortho position, resulting in a maximum C6/C2 hydroxylation ratio of 6.7. Upon increasing the pH, the total rate of conversion increases. Also, the C2 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 18 publications
2
22
0
Order By: Relevance
“…This is supported by linear free energy-type correlations, which indicate that the flavin C(4a) group behaves as an acid (5,6). Studies with fluorinated phenols (7) and theoretical calculations on the reactivity of the peroxide (8) also are consistent with this type of mechanism. However, experimental evidence allowing the unequivocal identification of a specific mechanistic variant for the monooxygenation step has not yet emerged.…”
mentioning
confidence: 69%
“…This is supported by linear free energy-type correlations, which indicate that the flavin C(4a) group behaves as an acid (5,6). Studies with fluorinated phenols (7) and theoretical calculations on the reactivity of the peroxide (8) also are consistent with this type of mechanism. However, experimental evidence allowing the unequivocal identification of a specific mechanistic variant for the monooxygenation step has not yet emerged.…”
mentioning
confidence: 69%
“…A less negative E(HOM0) can be expected to result in a stronger interaction between the substrate HOMO and the C(4a)-hydroperoxyflavin lowest unoccupied molecular or- Molecular orbital characteristics of phenol derivatives of importance for nucleophilic attack by the reactive electrons of the phenol on the C(4a)-hydroperoxyflavin intermediate, as calculated by The calculated HOMO characteristics of the various phenol derivatives are presented in Table 5. Values for both the protonated and the deprotonated forms of the phenol derivatives are presented, because results of a previous study demonstrated that the phenolic substrates are likely to become partially deprotonated upon binding to the active site of phenol hydroxylase [23].…”
Section: Molecular Orbital Characteristics Of the Substituted Phenolsmentioning
confidence: 99%
“…After substrate hydroxylation, the C4a-hydroxyflavin is formed. [43] In the final stage of the reaction (Figure 2) [44,45] In contrast to PHBH, PHHY shows significant uncoupling of substrate hydroxylation, even with the physiological substrate. [44] A slow hydroxylation rate is the main cause of the unproductive formation of hydrogen peroxide.…”
Section: Introductionmentioning
confidence: 99%